Pain as a Symptom of Mental Health Conditions Among Undocumented Migrants in France: Results From a Cross-Sectional Study - Sohela Moussaoui; Sohela Moussaoui; Sohela Moussaoui; Nicolas Vignier; Nicolas Vignier; Nicolas Vignier; Stephanie Guillaume; Florence Jusot; Florence Jusot; Antoine Marsaudon; Jérôme Wittwer; Jérôme Wittwer; et al. (International Journal of Public Health)
ObjectivesThis study aimed to explore the associations between mental health status and experienced pain among undocumented migrants (UMs) in France.MethodsWe used data from the multicentric cross-sectional “Premier Pas” study conducted in the Parisian and Bordeaux regions from February to April 2019. Participants over 18 years of age were recruited from sixty-three sites. Pain was assessed through two variables: overall pain and musculoskeletal pain. Mental health conditions, including anxiety, sleep disorders, depression, and posttraumatic stress disorder (PTSD) were evaluated. Logistic regression models were used to explore associations, controlling for social determinants of health (SDHs).ResultsOur findings revealed significant associations between mental health status and pain among the 1,188 included participants. Sleep disorder was associated to higher odds of musculoskeletal pain (aOR = 2.53, 95% CI [1.20–5.33], p = 0.014). Stratified results indicated that among women, depression was associated to higher odds of pain (aOR = 4.85, 95% CI [1.53–13.36], p = 0.007).ConclusionThis large study confirms the connection between mental health status and pain among UMs, providing valuable evidence for clinicians to address mental health issues in this population.